2021
DOI: 10.4314/rjmhs.v4i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Cervical Cancer Screening and Associated Factors Among Women Attending Outpatient Services in Rwamagana Hospital, Rwanda

Abstract: BackgroundCervical cancer is a global public health threat for women. Rwanda Ministry of Health recommends screening as preventive strategy. However, the screening remains low in Rwanda.ObjectiveTo determine the uptake level of cervical cancer screening and associated factors among Rwandan women.MethodsA quantitative analytical cross-sectional study design was used. We recruited 178 participants using convenience sampling from an estimated 320 women who attended outpatient department in the previous month. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Prior studies done in different part of Rwanda, although they used different study design to ours, they have reported varying degree of knowledge related to cervical cancer existence, its prevention and screening methods. 17 , 18 , 23 However, none of them has reported health promotion efforts such as the use of SMS, radio station broadcasts, and other telecommunication tools, as possible motivators or sources of information and knowledge related to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies done in different part of Rwanda, although they used different study design to ours, they have reported varying degree of knowledge related to cervical cancer existence, its prevention and screening methods. 17 , 18 , 23 However, none of them has reported health promotion efforts such as the use of SMS, radio station broadcasts, and other telecommunication tools, as possible motivators or sources of information and knowledge related to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…14 Different studies about cervical cancer screening in Rwanda reported a participation rate ranging from 2.6% to 28.3%. 15,[17][18][19] For example, Mukanyangezi et al 19 reported that only 7% in HIV-negative women and 27% in HIVpositive women have ever participated in cervical cancer screening. The aim of this study was to elucidate knowledge, barriers and motivators that may affect Rwandan women in using cervical cancer screening services, in order to improve the overall utilization of this program and thus contribute to the prevention of cervical cancer.…”
mentioning
confidence: 99%
“…Evidence supports the nding that inequalities in these underserved cervical pre-cancer screening countries favoured women who were older, resided in urban areas, were more educated and in the highest wealth quintile than younger women, who lived in rural areas, were uneducated and in the lowest wealth quintile [9,17,18]. Studies conducted in Ethiopia, Rwanda, Tanzania, Zambia, and Zimbabwe, also support this nding [10,27,28,12,29,11,12,13,14,15]. A study of 18 resource-constrained countries, of which eight were from sub-Saharan Africa further found that wealth status increased socioeconomic inequalities in cervical pre-cancer screening, whereas being married, unemployed and living in urban communities reduced it [9].…”
Section: Discussionmentioning
confidence: 58%
“…The sample size of females aged 25-49 years ranged from 5882 in Ethiopia to 9186 in Tanzania. The median age and interquartile ranges were 32 years (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in Ethiopia, 33 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Zambia and 34 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Malawi, Rwanda, and Tanzania. The rate of self-reported cervical pre-cancer screening was lowest in Rwanda (3.5% [95% CI 3.1%-4.0%]) and highest in Zambia (17.1% [95% CI 15.8%-18.5%]) and Zimbabwe (17.4% [95% CI 16.1%-18.8%]).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supports the finding that inequalities in these underserved cervical precancer screening countries favoured women who were older, resided in urban areas, were more educated and in the highest wealth quintile than women who were younger, who lived in rural areas, were uneducated and in the lowest wealth quintile 9 17 18. Studies conducted in Ethiopia, Rwanda, Tanzania, Zambia and Zimbabwe, also support this finding 10–15 34–36. A study of 18 resource-constrained countries, of which eight were from sub-Saharan Africa further found that wealth status increased socioeconomic inequalities in cervical precancer screening, whereas being married, unemployed and living in urban communities reduced it 9.…”
Section: Discussionmentioning
confidence: 71%